PENGARUH IKLAN, KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN MINUMAN YAKULT DI KOTA LHOKSEUMAWE (Studi Konsumen Yakult Pada Mahasiswa Universitas Malikussaleh Kampus Bukit Indah) - Puspa Indah Sari; Sufi Sufi (Negotium: Jurnal Ilmu Administrasi Bisnis, 2021)
This study aims to look the effect of advertising, product quality, price and brand image on purchasing decisions of yakult drinks for students at Malikussaleh University, Bukit Indah Campus. This research is a survey research. The population in this study were students of Malikussaleh University, Bukit Indah Campus, and the sample in this study were active students of the Business Administration study program at Malikussaleh University using the Slovin formula, which is a sampling technique that uses a critical value or accuracy limit of 0.1, so that the sample is obtained in This study amounted to 55 respondents from a total population of 120 students. The questionnaire test consisted of validity testing using the Product Moment method and reliability testing using the Cronbach's Alpha method. This study uses multiple regression analysis techniques with hypothesis testing using the SPSS 25 program. The results of this study indicate that advertising, product quality, price and brand image have an effect on purchasing decisions for yakult drinks at Malikussaleh University students, Bukit Indah Campus.